(untitled) (Annals of Medical Research, 2022)
Aim: Malignant middle cerebral artery (MCA) infarctions and severe traumatic brain injuries (TBI) can cause increased intracranial pressure (ICP), herniation, and eventually lead to death. Decompressive craniectomy (DC) can be life-saving in these patients. The present study aims to investigate the predictive factors for mortality in patients undergoing DC due to malignant MCA infarction and severe TBI. Material and Methods: Between January 2015 and January 2020, clinical and imaging findings, demographic characteristics and laboratory results of patients who underwent DC due to severe TBI and malignant MCA infarction were retrospectively analyzed and recorded for statistical analysis. In order to identify the most significant parameter in relation to mortality, a receiver operating characteristic (ROC) analysis was performed, and the area under the ROC curve was calculated. Results: The study included 30 patients undergoing DC. Out of 12 patients with TBI and 18 with malignant MCA infarction, 6 (50%) and 15 (83.3%), respectively, died. There was no statistically significant difference between survivors and non-survivors in terms of age and gender (p = 0.625 and p = 0.626). Patients who did not survive had significantly lower Glasgow coma scale (GCS) scores than survivors (p = 0.001). Moreover, the degree of midline shift, C-reactive protein-to-albumin ratio (CAR) and red blood cell distribution width (RDW-SD) levels were significantly higher in non-survivors than in survivors (p = 0.017, p = 0.002, and p = 0.009, respectively). The AUC values were as follows: GCS = 0.876 (95% Confidence Interval (CI), 0.733-1), CAR = 0.844 (95% CI, 0.706-0.982), RDW-SD = 0.796 (95% CI, 0.637-0.955), and amount of shift 0.775 (95% CI, 0.602-0.948). Conclusion: The present study found that patients with low GCS, an increased degree of midline shift, and high CAR and RDW-SD values benefit less from DC. It was considered that high CAR and RDW-SD could be a predictive marker for mortality.